A Molar Pregnancy within the Fallopian Tube. (4th December 2016) - Allen, Laura; Dawson, Charlotte; Nascu, Patricia; Rouse, Tyler
Abstract : Background . Discussion of the incidence of molar pregnancy and ectopic pregnancy. Role of salpingostomy and special considerations for postoperative care. Case . The patient is a 29-year-old G7P4 who presented with vaginal bleeding in the first trimester and was initially thought to have a spontaneous abortion. Ultrasound was performed due to ongoing symptoms and an adnexal mass was noted. She underwent uncomplicated salpingostomy and was later found to have a partial molar ectopic pregnancy. Conclusion . This case illustrates the rare occurrence of a molar ectopic pregnancy. There was no indication of molar pregnancy preoperatively and this case highlights the importance of submitting and reviewing pathological specimens.